Analysis of Corrosion Using Natural Disperse in a Water Emulsion, Palm Oil Acts as a Corrosion Inhibitor - Bharathi, Satheisvaran; Zakaria, Hanis; Koshy, Anelka John (Research Progress in Mechanical and Manufacturing Engineering, 2026)
A mild steel sample piece was dissolved in a 1M HCl solution, and potentiodynamic polarization curve measurements were used to create a palm oil in water emulsion that acted as a corrosion inhibitor. A three-electrode arrangement was employed, consisting of a working, reference, and counter electrode. Platinum served as the counter electrode, silver chloride (AgCl) served as the reference electrode, and mild steel served as the working electrode. The purpose of the study was to determine whether a mild steel sample piece could be utilized as a corrosion inhibitor by using a water emulsion containing palm oil. Additionally, the study aimed to determine the maximal inhibitor efficiency and capability of palm oil in water emulsion as a mild steel corrosion inhibitor.